Axial vs. Equatorial Ligand Rivalry in Controlling the Reactivity of Iron(IV)‐Oxo Species: Single‐State vs. Two‐State Reactivity. Issue 26 (25th April 2018) - Kumar, Ravi; Ansari, Azaj; Rajaraman, Gopalan
Abstract: High‐valent iron‐oxo species are known for their very high reactivity, and this aspect has been studied in detail over the years. The role of axial ligands in fine‐tuning the reactivity of the iron(IV)‐oxo species has been particularly well studied. The corresponding role of equatorial ligands, however, has rarely been explored, and is of prime importance in the development of non‐heme chemistry. Here, we have undertaken detailed DFT calculations on [(L NHC )Fe IV (O)(CH3 CN)] 2+ (1 ; L NHC =3, 9, 14, 20‐tetraaza1, 6, 12, 17‐tetraazoniapenta‐cyclohexacosane‐1(23), 4, 6(26), 10, 12(25), 15, 17(24), 21‐octaene) in comparison to compound II of cytochrome P450 [(porphyrin)Fe IV (O)(SH)] − (2 ) to probe this aspect. The electronic structures of1 and2 are found to vary significantly, implying a large variation in their reactivities. In particular, the strong equatorial ligand present in1 significantly destabilizes the quintet states as compared to species2 . To fully understand the reactivity pattern of these species, we have modelled the hydroxylation of methane by both1 and2 . Our calculations reveal that1 reacts via a low‐lying S =1 π pathway, and that the generally available S =2 σ pathway is not energetically accessible. In addition to having a significant barrier for C−H bond activation, the ‐OH rebound step is also computed to have a large barrier height, leading to a marked difference in reactivity between these two species. Of particular relevance here is the observation of pure triplet‐state reactivity for1 . We have also attempted to test the role of axial ligands in fine‐tuning the reactivity of1, and our results demonstrate that, in contrast to heme systems, the axial ligands in1 do not significantly influence the reactivity. This highlights the importance of designing equatorial ligands to fine‐tune reactivity of high‐valent iron(IV)‐oxo species. Abstract : Importance of equatorial ligation : Strong equatorial ligation suppresses two‐state reactivity of iron(IV)‐oxo species (see graphic). This suggests a means of fine‐tuning the reactivity of Fe IV =O species using equatorial ligands.